Importance of intercultural dialogue in tourism development in Totonaca indigenous communities - Ortíz Rodríguez, Ma. Teresa Tonantzin; Sandoval Quintero, Mayra Antonieta (Annals of Anthropology, 2021)
A critical stance shows the impacts of conventional and alternative tourism as an imposition emerging measure of economic improvement for indigenous peoples. The study aims to provide a first approach to the theoretical and methodological bases of the use of intercultural dialogue. The method considers as indicator the dialogue to minimize the sociocultural effects of a tourism proposal. The fundamental axis of the research is the relevance of the indigenous in deciding harness their biocultural heritage as a tourism attraction, in this study, for the Totonacos of Lipuntahuaca, municipality of Huehuetla, Puebla.